PERMASALAHAN MEMBACA DAN MENULIS DI KB DAN TK - Tadkiroatun Musfiroh (Jurnal Penelitian Humaniora, 2007)
Many parents and teachers do not realize the negative effect of formal teaching of educators fro children. This is a dilemmatic problem which is difficult to solve. This research aims at to describe reading and writing initiation in playgroup and kindergarten. The subjects of the research are 171 people, 87 people are from DIY and the rest, 84, are from Central Java. Data are taken using observation, interview, questionnaire, and documentation. Further techniques employed are note and record, and orthographic transcription. Data are analyzed descriptively and qualitatively. Validity is kept by employing (1) method of double data gathering, (2) long observation, and (3) discussion among the researchers. The research result shows that (1) the initiation process of reading and writing can be divided into 4; forming and pronouncing the alphabets, inscribing phonemic awareness, applying directly to form of word, and applying directly to the spelling of the syllabi, word, and phrase. (2) Forms of receptive initiation of written language are through alphabet memorizing, identifying form of alphabets, story reading, spelling practice, instruction of reading books, and displaying media. Forms of productive initiation of written language are through various ways of letter to letter initiation, initiation of syllabi and word, and children’s involvement. (3) to motivate the children, teachers analyze and find solution which is mature in nature, methodic, and strategic